Emotional Intelligence and Critical Thinking Motivation among Nursing Students: Exploring Key Predictors and Demographic Influences - Alshowkan, Amira (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Emotional intelligence (EI) and critical thinking motivation (CTM) are crucial for nursing students’ development, particularly in patient care and clinical decision-making. However, empirical evidence on these constructs remains limited among nursing students in Saudi Arabia.Purpose: This study aimed to investigate the relationship between EI and CTM among nursing students and to explore demographic variations and predictors of CTM.Methods: This cross-sectional study included 215 undergraduate students from Saudi Arabia, recruited via convenience sampling. EI was assessed using the Schutte Self-Report Emotional Intelligence Test, and CTM was measured using the Critical Thinking Motivational Scale (CTMS). Data were analyzed using descriptive statistics, Chi-square tests, and multiple regression, with the significance level set at p < .05.Results: A total of 215 participants were included in the analysis. EI and CTM scores varied, with 51.6% of participants exhibiting moderate levels of both. Higher EI was significantly associated with higher CTM scores (χ² = 29.9, p < .001), with students with low EI demonstrating lower CTM and those with high EI demonstrating higher CTM. Demographic analysis showed that EI was higher among students living with their families (p = .01), while CTM scores were higher among older students (p = .019) and those in higher academic years (p < .001). Multiple regression identified EI, education level, and residence as positive predictors of CTM, while male gender was a negative predictor (R² = .29, p < .001).Conclusion: These findings indicate that EI is significantly associated with CTM, suggesting that promoting EI and fostering supportive learning environments may enhance students’ motivation to engage in critical thinking and contribute to their academic and professional development. Future research should employ longitudinal and intervention designs to examine causal relationships and explore potential mediating factors.